2020
DOI: 10.1038/s41533-020-00189-6
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of modifiable factors limiting treatment efficacy of poorly controlled asthma patients: EFIMERA observational study

Abstract: Several modifiable factors leading to poor asthma control have been described. We aimed to determine the proportion of patients with inadequate treatment, adherence to it, or critical mistakes with inhaler technique, and their impact on asthma control. We conducted a cross-sectional multicenter observational study including asthma patients referred from primary to specialist care for the first time. Data collected were adequate prescription according to guidelines, treatment adherence, and disease control. Of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…7,8 Another study revealed that in-adequate prescription, non-adherence to treatment and inhaler misuse were responsible factors for bad asthma control. 10 House-dust was proven to be associated with asthma in our study as also various guidelines on immunotherapy in Asthma. 11 As per the study on children done by Okasha et al, 12 sensitisation to house dust mite increased asthma severity and decreased the ability to control symptoms.…”
Section: Discussionsupporting
confidence: 53%
“…7,8 Another study revealed that in-adequate prescription, non-adherence to treatment and inhaler misuse were responsible factors for bad asthma control. 10 House-dust was proven to be associated with asthma in our study as also various guidelines on immunotherapy in Asthma. 11 As per the study on children done by Okasha et al, 12 sensitisation to house dust mite increased asthma severity and decreased the ability to control symptoms.…”
Section: Discussionsupporting
confidence: 53%
“…All in all, the available data support the assumption that the Easyhaler presents benefits which include consistency of dose [ 43 ], achievement of optimal PIFR [ 51 ], few critical errors in use [ 49 ], and overall high patient satisfaction [ 33 , 37 ]. Moreover, reduction in emissions of greenhouse gases was shown compared to MDIs.…”
Section: Discussionmentioning
confidence: 99%
“…Critical errors of inhaler use related strongly to poor asthma control (OR 3.03, 95% CI 2.18–4.21) (Fig. 5 ) [ 49 ].
Fig.
…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigators also found that an absence of inhaler technique review in the past 12 months was strongly associated with severe error in inhaler technique 13 . Studies have reported modifiable risk factors that affect respiratory disease state control, poor inhaler adherence, inappropriate prescriptions, and inhaler misuse 14,15 . Commonly reported errors in inhaler use include failure to exhale before inhaling, 13,16 failure to hold breath, 13,16 insufficient force of inhalation, 13 failure to pierce button completely, 16 not holding the inhaler upright, 16 and failure to gargle after inhalation 16 .…”
Section: Introductionmentioning
confidence: 99%